The Determinants of the European Banking Crisis - Zidi, Sana; Regaieg, Boutheina; Hamzaoui, Nessrine (International Journal of Economics and Financial Issues, 2021)
The fragility of the European banking system in recent years has motivated us to research on the main indicators that weigh on the soundness of its banking institutions and therefore deserves special attention from supervisors. Our study is based on 40 consolidated banking groups from 10 countries in Europe. We used binary logistic regression as an econometric model. We introduced accounting, macroeconomic, regulatory, legal and institutional variables. The results of our study confirm that doubtful credit is the main variable contributing to the birth of the European banking crisis. Keywords: banking crisis, binary Logit model, legal, regulatory and institutional environment. JEL Classifications: E58, C15, P48. DOI: https://doi.org/10.32479/ijefi.11225